2009
DOI: 10.1021/jp903331w
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Modeling of Voiding Mechanisms at Oxide/Alloy Interfaces

Abstract: For the first time, voiding mechanisms resulting from the condensation of atomic vacancies injected at oxide/alloy interfaces by the growth of oxide layers have been studied by means of periodic density functional theory (DFT) calculations. Several interfaces were built by superimposing ultrathin films of alumina on the γ-TiAl(111) surface, and their relative stabilities were compared by calculating the interface energy variation. The formation energy of single Ti or Al vacancies and clustered and dispersed en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…For such reasons, simulation on multiple component systems such as alloy is much more challenging than single component models. Theoretical studies of alloy system is either limited in the small scale at the framework of DFT calculations [146], or at the level of grain boundaries with less atomistic information [147,148]. Force field simulations of alloy models is still at its early stage [149].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…For such reasons, simulation on multiple component systems such as alloy is much more challenging than single component models. Theoretical studies of alloy system is either limited in the small scale at the framework of DFT calculations [146], or at the level of grain boundaries with less atomistic information [147,148]. Force field simulations of alloy models is still at its early stage [149].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…An advantage of SECM is its capability to probe charge transfer occurring nonuniformly at interfaces [13,14]. Scanning reference electrode technique (SRET) has been used for determination of the potential distribution on corroding surfaces [15][16][17][18][19][20] and scanning tunneling microscope (STM) is a technique to study corrosion at micro-and nano-scale [21][22][23][24]. Zhu et al [10] investigated the impact of tensile and compressive stress on reactivity of the Alloy 800 C-ring sample using SECM and found that both tension and compression increased the localized surface reactivity, indicating corrosion susceptibility of Alloy 800 under stress in thiosulfate-contained chemistries.…”
Section: àmentioning
confidence: 99%
“…Mott-Schottky measurements were also used to investigate the electric properties as well as the susceptibility to the presence of chloride ions and tensile stress of passive films. Marcus et al investigated the passive film growth mechanism at nano scale using STM combined with molecular dynamics simulation [22,23,[26][27][28][29]. Limited studies of thiosulfate-chloride induced passivation degradation were performed using a combination of techniques [10].…”
Section: àmentioning
confidence: 99%
“…This is extensively accompanied by the nucleation and coarsening of oxide cavities as well as cracking, presenting potential weaknesses in the oxide microstructural integrity permitting liquid solder ingress into the metal/oxide interface. The evolution of the nanosized cavities into micron-sized, isolated voids imply a history of Ostwald ripening through the Kirkendall effect [30], where oxygen vacancies diffuse and supersaturate around existing void surfaces, subsequently into precipitation and further coalescence [31]. From 12 hr to 16 hr, the Sn thin film surface had attained full coverage of the rough 'oxide patch' morphology.…”
Section: Surface Oxidation As a Wetting Barriermentioning
confidence: 99%